Effect of Different Drying Conditions on Proximate Compositions of Red- and Yellow-Fleshed Watermelon Rind Powders - Ho, Lee Hoon (2016)
This study aimed to investigate the effect of different drying conditions (hot-air oven drying at 40 ⁰C and 60 ⁰C, and freeze drying) on nutritional quality of red- and yellow-fleshed watermelon rinds. The proximate compositions, carbohydrate content, and energy value of watermelon rind powders were determined. Freeze drying method preserved more nutrients followed by hot-air oven drying at 40 ⁰C and 60 ⁰C for red-fleshed watermelon rind powder. The freeze dried powder contains 18.86% moisture, 19.13% ash, 11.82% crude protein, 22.02% crude fiber, 2.21% crude fat, 47.77% carbohydrate, and 259.13 kcal of energy. Hot-air oven drying at 40 ⁰C was the most effective method to preserve the nutrient of yellow-fleshed watermelon rind powder with chemical compositions of 15.12% moisture, 20.57% ash, 13.37% crude protein, 14.34% crude fiber, 0.70% crude fat, 50.31% carbohydrate, and 260.72 kcal of energy. Results suggest that freeze drying and hot-air oven drying (40 ⁰C) methods had the highest potential to be applied in processing of red- and yellow-fleshed watermelon rind powders, respectively.